A New Type of Allodiploid Hybrids Derived From Female Megalobrama amblycephala × Male Gobiocypris rarus - Liu, Qingfeng; Zhang, Xuanyi; Liu, Junmei; Liu, Fanglei; Shi, Fangming; Qin, Qinbo; Tao, Min; Tang, Chenchen; Liu, Shaojun (Frontiers in Genetics, 2021)
Distant hybridization can combine whole genomes from parent species and result in changes in the phenotypes and genotypes in the hybrids. The characteristics of many hybrid fishes with even number chromosomes have been reported, but the hybrids with odd number chromosomes are rarely reported. Blunt snout bream (Megalobrama amblycephala, BSB, 2n = 48) and rare gudgeon (Gobiocypris rarus, RG, 2n = 50) belong to two different subfamilies and have quite different biological characteristics. In this study, we obtain the hybrids (BR) derived from the inter-subfamily hybridization of female BSB and male RG. We investigate the fertilization rate, hatching rate, morphological traits, chromosomal numbers, DNA content, growth rates and 5S rDNA in the BR. The results show that the BR is allodiploid fish with 49 chromosomes, all the measurable traits are significantly different (P<0.05) among BR, BSB and BR, indicating that BR has an obvious hybrid characteristic. Interestingly, the upper part of the BR body color is similar to BSB (gray), the lower part of the BR body color is similar to RG (light yellow), and the BR inherits unique light yellow wide longitudinal band from the RG. Furthermore, the BR has a fast growth rate compared with RG. The 5S rDNA of the BR inherits the specific bands of its parental 5S rDNA respectively and has some mutations, which show obvious recombination, heredity, and variability in BR. This study will be of great significance in fish genetic breeding.